Penerapan Manajemen Kepagawaian di Pondok Pesantren Royatul Qur’an Batam - M.Nurman Ardiansyah; Hasbi Indra; Abdul Hayyie Al Kattani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Islamic boarding schools play a major role, namely, as motivators, innovators, and community dynamists so that the relationship between pesantren and the community becomes harmonious, as a result, the existence and presence of Islamic boarding schools in community empowerment become stronger. The purpose of this journal is to see the success of the Royatul Qur’an Boarding School in implementing personnel management with reference to seven main activities, namely recruitment (personnel procurement), personnel development and development, personnel promotion and transfer, compensation for personnel, personnel welfare, personnel evaluation, termination of employment. employment relationship (PHK). This type of research is field research, namely research conducted with the direct aim of excavating and researching data relating to the effectiveness of the implementation of personnel management and what factors influence the implementation of personnel management at the Royatul Qur’an Integrated Islamic Boarding School in Batam. This research was conducted in November 2022. The results of the study after conducting interviews and collecting related data, the Royatul qur’an Integrated Islamic Boarding School has implemented all the main activities of personnel management in a well-managed and managed manner.